Upper Extremity Muscle Activation during Recovery of Reaching in Subjects with Post-stroke Hemiparesis - Wagner, Joanne M. (2006)
OBJECTIVE: To investigate upper extremity muscle activation and recovery during the first few months after stroke. METHODS: Subjects with hemiparesis following stroke were studied performing a reaching task at an acute time point (mean = 9 days post-stroke) and then again at a subacute time point (mean = 109 days post-stroke). We recorded kinematics and electromyographic activity of 6 upper extremity muscles. RESULTS: At the acute time point, the hemiparetic group had delayed muscle onsets, lower modulation ratios, and higher relative levels of muscle activation (%MVIC) during reaching than controls. From the acute to the subacute time points, improvements were noted in all three variables. By the subacute phase, muscle onsets were similar to controls, while modulation ratios remained lower than controls and %MVIC showed a trend toward being greater in the hemiparetic group. Changes in muscle activation were differentially related to changes in reaching performance. CONCLUSIONS: Our data show that improvements in muscle timing and decreases in the relative level of volitional activation may underlie improved reaching performance in the early months after stroke. SIGNIFICANCE: Given that stroke is one of the leading causes of persistent physical disability, it is important to understand how the ability to activate muscles changes during the early phases of recovery after injury.